2019
DOI: 10.1186/s12905-019-0828-9
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Champion Health Belief Model to determine beliefs and behaviors of Turkish women academicians regarding breast cancer screening: A cross sectional descriptive study

Abstract: BackgroundBreast cancer is an important cancer type and the most common malignancy among women in both developed and developing countries and the second leading cause of cancer death in women worldwide. This study aimed to examine the projected risk of breast cancer in Turkish women academician, determine the levels of their breast cancer screening behaviors and uncover the relationship between their health beliefs and screening behaviors.MethodsThis cross-sectional descriptive study was conducted from March t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
30
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 23 publications
4
30
1
2
Order By: Relevance
“…Studies have shown that most Turkish women do not perform regular BSE (17,18). [26]. Both findings were lower than our study as well.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Studies have shown that most Turkish women do not perform regular BSE (17,18). [26]. Both findings were lower than our study as well.…”
Section: Discussioncontrasting
confidence: 94%
“…Furthermore, self-efficacy was the only determinant factor on the behavior of BSE. But some studies observed that sensitivity, health motivation, benefits of BSE, barriers to BSE subscales influenced the performing of BSE (26)(27)(28)(29). Demirkıran et al found that the age and profession effect BSE performance (30).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the barriers carry significant risk factors for women not undergoing mammograms (OR: 0.905, p: 0.012). This finding is consistent with a study done in Turkey in 2019, which concluded that females who underwent mammography had lower barriers to mammography compared to females who did not [ 7 ].…”
Section: Discussionsupporting
confidence: 92%
“…In a study conducted in Turkey in 2019, the mean age of the participants was 36.1 ± 0.53 years (n = 200); most of them were between 30-40 years (51.5%). A majority of the subjects were married (57%), and only 7% were aware of having a positive family history among first-degree relatives [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the perceived knowledge sub-dimension of the Breast Cancer Perception Scale has not been measured before, according to the authors' knowledge, and it is a unique scale that measures a person's breast cancer knowledge perception. The Health Belief Model is commonly used to explain breast cancer diagnosis behaviors (11)(12)(13)(14). Therefore, this scale development study was based on the Health Belief Model.…”
mentioning
confidence: 99%